Ab initio interatomic decay widths of excited states by applying Stieltjes imaging to Lanczos pseudospectra - Kopelke, Sören; Gokhberg, Kirill; Averbukh, V.; Tarantelli, F.; Cederbaum, Lorenz S. (The journal of chemical physics, 2011)
Electronically excited states of atoms and molecules in an environment may decay in interatomic processes by transferring excess energy to neighboring species and ionizing them. The corresponding interatomic decay width is the most important characteristic of the decay allowing to calculate its efficiency and the final states’ distribution. In this paper we present calculations of interatomic widths by the Fano-Stieltjes method applied to Lanczos pseudospectra, which has been previously shown to provide accurate autoionization widths in atoms and molecules. The use of Lanczos pseudospectra allows one to avoid the full diagonalization bottleneck and makes the method applicable to larger systems. We apply the present method to the calculation of interatomic decay widths in NeMg, NeAr and HCN·Mgn, n = 1, 2 clusters. The results are compared with widths obtained analytically and by other ab initio methods where available.
Gesehen am 07.07.2022